iDAI.thesauri - Thänert, Sabine; Colombi, Camilla; Vitt, Lena (e-Forschungsberichte des DAI, 2017)
The project iDAI.thesauri aims to develop a „DAI-worldwide thesaurus“ which is intended to merge vocabularies already in use throughout the libraries and projects of the German Archaeological Institute according to the guidelines of DARIAH-EU (https://www.dariah.eu/).